Validity of maternal report on birth weight 11 years after delivery: the 1993 Pelotas Birth Cohort Study, Rio Grande do Sul State, Brazil Validade do relato materno de peso ao nascer 11 anos após o parto: Coorte de Nascimentos de 1993 em Pelotas, Rio Grande do Sul, Brasil - Cora L. P. Araújo; Carmem L. C. Dutra; Pedro C. Hallal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Birth weight has short and long-term effects on health. Some studies have used retrospective data on birth weight, reported by the subject or by the parents. This paper compares data on birth weight measured by the research team in 1993 with birth weight reported by the mother in 2004-2005, using data from the 1993 Pelotas Birth Cohort Study, Rio Grande do Sul State, Brazil. We also evaluate the role of misclassification when exploring the effect of birth weight on a given outcome. Mean difference between the two variables was 20g (SD = 288.3). Agreement for detecting low birth weight was 95.2% in the sample as a whole (kappa = 0.73), but was lower among low-schooling mothers. Mothers of children weighing less than 3,500g at birth tended to overestimate the child's birth weight. Inversely, mothers of heavier children tended to underestimate the values. One out of four mothers reported a difference of at least 200g in birth weight as compared to that measured in 1993. Use of reported birth weight diluted the magnitude of the association with body mass index at 11 years in comparison with measured birth weight. Reported birth weight should be used with great caution, if at all. O peso ao nascer exerce efeitos em curto e longo prazo sobre a saúde. Alguns estudos usam dados retrospectivos sobre o peso ao nascer, relatado pelo indivíduo ou pelos pais. Neste artigo nós comparamos o peso ao nascer medido em 1993 pela equipe de pesquisa com o relatado pela mãe em 2004-2005, usando-se dados da Coorte de Nascimentos de 1993 em Pelotas, Rio Grande do Sul, Brasil. Também avaliamos o papel do erro de classificação quando se explora a associação entre peso ao nascer e um determinado desfecho. A diferença média entre as duas variáveis foi de 20g (DP = 288,3). O percentual de concordância para a detecção de baixo peso ao nascer foi de 95,2% na amostra total (kappa = 0,73), mas foi menor entre as mães com baixa escolaridade. As mães de crianças que nasceram com menos de 3.500g tenderam a superestimar o peso ao nascer de seus filhos, enquanto as mães de crianças que nasceram com mais de 3.500g tenderam a subestimar o peso ao nascer de seus filhos. Uma em cada quatro mães relatou um peso ao nascer mais de 200g diferente do que foi medido em 1993. O uso do peso ao nascer relatado diluiu a associação com índice de massa corporal aos 11 anos de idade quando comparado ao peso ao nascer mensurado. O peso ao nascer relatado deve ser usado (se for usado) com muita cautela nessa população.